Battery and method of manufacturing the same
Patent Information
- Application Number
- CN202511604068.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-04
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2045-11-04
AI Technical Summary
但是由于本身动力学较差的硅基材料处于下层,会进一步恶化负极体系动力学,若将硅基材料置于上层,硅基材料可最先接触电解液进而接受锂离子,虽能提高负极体系动力学,但由于硅基材料在极片表层初始成膜对活性锂消耗更高,且后续过大的体积应变效应,也更容易对表界面SEI膜破坏与里界面连接造成断开,从而恶化长期快充循环性能
在本申请实施例中,所提供的电池负极片,第一负极涂层中的第一聚合物存在于第一负极涂层的表层,第一负极涂层表层的下方为碳基材料层,第二负极涂层中的第二聚合物存在于第二负极涂层的表层,第二负极涂层表层的下方为硅基材料层。其中,第一聚合物和第二聚合物会对第二负极涂层中的硅基材料层完成包覆,由此避免了第二负极涂层中硅基材料层的过高活性锂消耗和过大的体积应变效应带来的低首效和SEI(固体电解质界面)膜破坏,并保证了负极体系动力学,改善快充循环寿命。因此,电池具有较高首效以及较高的快充循环寿命。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery technology, and more specifically, to a battery and a method for preparing the same. Background Technology
[0002] In recent years, with the development of portable electronic devices and the increasing demand for electric vehicles, the energy density of current lithium-ion batteries has gradually failed to meet people's needs, making the development of high-energy-density lithium-ion batteries an urgent task.
[0003] Silicon anode materials are widely recognized as next-generation lithium-ion battery anode materials due to their high specific capacity and low potential. However, silicon-based materials experience significant volume expansion during charge and discharge, which can easily damage the electrode structure. Furthermore, compared to traditional graphite lithium-ion anodes, silicon anodes exhibit poorer kinetic performance. To address these shortcomings, existing technologies suggest a layered design for the active material layers of the anode containing graphite and silicon-based materials. This involves placing primary granular graphite and silicon-based materials in the first layer near the current collector, and secondary granular graphite in the second layer, reducing structural damage caused by the volume expansion of silicon-based materials. However, placing the inherently less kinetic silicon-based material in the lower layer further deteriorates the anode system's kinetics. While placing the silicon-based material in the upper layer allows it to contact the electrolyte first and accept lithium ions, improving the anode system's kinetics, the initial film formation on the electrode surface consumes more active lithium, and the subsequent excessive volume strain can more easily damage the surface SEI film and break the connection between the inner and outer interfaces, thus worsening long-term fast-charge cycle performance.
[0004] Therefore, there is an urgent need to provide a battery that can solve the defects of existing silicon-containing batteries, such as poor interface connection of the negative electrode sheet, poor dynamics of the negative electrode system, low initial efficiency, and low fast-charging cycle life. Summary of the Invention
[0005] In view of this, the present invention aims to at least partially solve one of the technical problems in the related art. To this end, the present invention provides a battery and a method for manufacturing the same, which has high initial efficiency and high fast-charge cycle life.
[0006] To solve the above-mentioned technical problems, this application is implemented as follows: According to one aspect of this application, an embodiment of this application provides a battery, including a positive electrode, a separator, a negative electrode, and an electrolyte, wherein the negative electrode includes: current collector; A first negative electrode coating is disposed on at least one side surface of the current collector along the thickness direction, and the first negative electrode coating comprises a first polymer and a first active material; The second negative electrode coating is disposed on the surface of the first negative electrode coating away from the current collector, and the second negative electrode coating includes a second polymer and a second active material; Wherein, the first polymer is located on the surface layer of the first negative electrode coating on the side away from the current collector; The second polymer is located on the surface of the second negative electrode coating on the side away from the first negative electrode coating; The first active material includes a carbon-based active material; the second active material includes a silicon-based active material.
[0007] In some of these embodiments, the first polymer is obtained by polymerizing a first polymeric monomer.
[0008] In some of these embodiments, the first polymeric monomer comprises an amino- and / or nitrile-containing polymeric monomer.
[0009] In some of these embodiments, the second polymer is obtained by polymerization of a second polymeric monomer.
[0010] In some of these embodiments, the second polymeric monomer comprises a long-chain unsaturated monomer.
[0011] In some of these embodiments, the first polymeric monomer includes at least one of acrylamide, N,N-dimethylacrylamide, acrylonitrile, and isocyanate.
[0012] In some embodiments, the second polymeric monomer includes at least one of methyl methacrylate, ethyl acrylate, and pentaerythritol acrylate.
[0013] In some of these embodiments, the mass of the first polymer is 3 to 5% of the mass of the silicon-based active material, based on the mass of the silicon-based active material.
[0014] In some of these embodiments, the mass of the second polymer is 1 to 3% of the mass of the silicon-based active material, based on the mass of the silicon-based active material.
[0015] In some embodiments, the carbon-based active material includes at least one of natural graphite and artificial graphite.
[0016] In some embodiments, the first negative electrode coating further includes a first conductive agent and a first binder.
[0017] In some of these embodiments, the mass ratio of the first polymer, the first active material, the first conductive agent, and the first binder is (0.6~3):(92~97):(1~3):(1~2).
[0018] In some embodiments, the areal density of the first negative electrode coating is 40-80 g / m³. 2 .
[0019] In some of these embodiments, the silicon-based active material content in the second active material is ≥20% by mass.
[0020] In some of these embodiments, the silicon-based active material includes at least one of a silicon-oxygen composite material or a silicon-carbon composite material.
[0021] In some embodiments, the second negative electrode coating further includes a second conductive agent and a second binder.
[0022] In some of these embodiments, the mass ratio of the second polymer, the second active material, the second conductive agent, and the second binder is (0.2~3):(92~98):(1~3)(1~2).
[0023] In some embodiments, the areal density of the second negative electrode coating is 30-60 g / m³. 2 .
[0024] According to another aspect of this application, embodiments of this application provide a method for preparing a battery, comprising the following steps: The positive electrode, separator, and negative electrode are arranged in sequence, wound up, injected with electrolyte, left to stand, and then formed and aged to obtain the battery. The electrolyte contains an initiator.
[0025] In some embodiments, the preparation of the negative electrode includes: A first negative electrode slurry is coated on at least one side of the current collector to obtain a first negative electrode coating. A second negative electrode slurry is coated on the surface of the first negative electrode coating to obtain a second negative electrode coating. The current collector coated with the first negative electrode coating and the second negative electrode coating is dried and cold-pressed.
[0026] In some of these embodiments, the first negative electrode coating comprises a first polymeric monomer and a first active material.
[0027] In some of these embodiments, the second negative electrode coating comprises a second polymer monomer and a second active material.
[0028] In some of these embodiments, the first polymeric monomer accounts for 0.6 to 3% of the total mass of the first negative electrode coating.
[0029] In some embodiments, the second polymeric monomer accounts for 0.2 to 3% of the total mass of the second negative electrode coating.
[0030] In some embodiments, the mass of the initiator is 0.1 to 0.5% of the total mass of the first and second polymeric monomers in the negative electrode.
[0031] In some embodiments, the initiator includes at least one of azobisisobutyronitrile, cumene hydroperoxide, tert-butyl hydroperoxide, di-tert-butyl peroxide, or persulfate.
[0032] In some of these embodiments, the settling temperature is 60-80°C and the time is 6-12 hours.
[0033] Implementing the technical solution of the present invention has at least the following beneficial effects: In this embodiment, the provided battery negative electrode sheet has a first polymer in the first negative electrode coating, which is located on the surface of the first negative electrode coating, and a carbon-based material layer is located below the surface of the first negative electrode coating. Similarly, a second polymer in the second negative electrode coating is located on the surface of the second negative electrode coating, and a silicon-based material layer is located below the surface of the second negative electrode coating. The first and second polymers completely coat the silicon-based material layer in the second negative electrode coating, thereby preventing excessive active lithium consumption and excessive volumetric strain effects that could lead to low initial efficiency and SEI (solid electrolyte interphase) film damage in the silicon-based material layer of the second negative electrode coating. This also ensures the dynamics of the negative electrode system and improves fast-charge cycle life. Therefore, the battery exhibits high initial efficiency and high fast-charge cycle life.
[0034] Additional aspects and advantages of this application will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of the invention. Detailed Implementation
[0035] The present application will be further described below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the present application.
[0036] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges or individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0037] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions.
[0038] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions.
[0039] Unless otherwise specified, all steps in this application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the mention that the method may also include step (c) indicates that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.
[0040] Unless otherwise specified, the terms "comprising" and "including" as used in this application can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.
[0041] In view of the shortcomings of existing silicon-based materials used in lithium battery anodes, this application provides a battery including a positive electrode, a separator, a negative electrode, and an electrolyte, wherein the negative electrode includes: current collector; A first negative electrode coating is disposed on at least one side surface of the current collector along the thickness direction, and the first negative electrode coating comprises a first polymer and a first active material; The second negative electrode coating is disposed on the surface of the first negative electrode coating away from the current collector, and the second negative electrode coating includes a second polymer and a second active material; Wherein, the first polymer is located on the surface layer of the first negative electrode coating on the side away from the current collector; The second polymer is located on the surface of the second negative electrode coating on the side away from the first negative electrode coating; The first active material includes a carbon-based active material; the second active material includes a silicon-based active material.
[0042] The provided negative electrode sheet has a multilayer structure, comprising a current collector, a first negative electrode coating, a second negative electrode coating, and a third negative electrode coating stacked sequentially. Specifically, the first negative electrode coating is disposed on at least one surface of the current collector, the second negative electrode coating is disposed on the surface of the first negative electrode coating, and the third negative electrode coating is disposed on the surface of the second negative electrode coating. The first negative electrode coating can serve as a silicon substrate, the second negative electrode coating can serve as an interface reinforcement layer, and the third negative electrode coating can serve as a carbon-based material layer, such as a graphite layer.
[0043] The phrase "the first negative electrode coating is disposed on at least one surface of the current collector along its thickness direction" means that the first negative electrode coating can be disposed on one surface of the current collector along its own thickness direction, or it can be disposed on two surfaces of the current collector along its own thickness direction. Here, "surface" can be the entire area of the current collector or a part of the current collector. As in this embodiment, the surface can be the entire area of the current collector. This application does not have any particular limitation in this regard, as long as the purpose of this application can be achieved.
[0044] As an example, the current collector has two surfaces opposite each other in its thickness direction, and a first negative electrode coating is disposed on the two opposite surfaces of the current collector. Further, a second negative electrode coating is formed on both surfaces of the first negative electrode coating. Even further, a third negative electrode coating is formed on both surfaces of the second negative electrode coating. It is understood that in other embodiments, the first negative electrode coating may also be laminated on either of the two surfaces of the current collector.
[0045] In this application, the material of the current collector in the negative electrode is not specifically limited.
[0046] In this application, the first polymer in the first negative electrode coating exists on the surface of the first negative electrode coating, and a carbon-based material layer lies beneath the surface of the first negative electrode coating. Similarly, the second polymer in the second negative electrode coating exists on the surface of the second negative electrode coating, and a silicon-based material layer lies beneath the surface of the second negative electrode coating. The first and second polymers completely coat the silicon-based material layer in the second negative electrode coating, thereby preventing excessively high active lithium consumption and excessive volumetric strain effects that could lead to low initial efficiency and SEI (solid electrolyte interphase) film damage in the silicon-based material layer of the second negative electrode coating. This also ensures the dynamics of the negative electrode system and improves fast-charging cycle life.
[0047] In some embodiments, the first polymer is obtained by polymerizing a first polymeric monomer.
[0048] In some embodiments, the first polymeric monomer includes amino- and / or nitrile-containing polymeric monomers. The mass of the first polymeric monomer is less than the mass of the first active material, and it spontaneously floats to the surface of the first coating during the coating process. The amino- and / or nitrile-containing polymeric monomers, after coating the second negative electrode coating, react with the hydroxyl groups in the silicon-based active material of the second negative electrode coating to form chemical bonds, thereby mitigating the adverse effects of the interface breakdown between the first and second negative electrode coatings caused by the volume strain of the silicon-based material during fast charging cycles. Furthermore, the first polymeric monomer also combines with the initiator in the subsequent electrolyte, undergoing a high-temperature reaction in the early stages of formation to polymerize in situ on the surface of the first negative electrode coating into a first polymer. Thus, the surface of the first negative electrode coating can be connected to the second negative electrode coating based on chemical bonds, further strengthening the connection between the first and second negative electrode coatings and ensuring the overall stability of the negative electrode in the later stages of cycling.
[0049] In some embodiments, the second polymer is obtained by polymerizing a second polymeric monomer.
[0050] In some embodiments, the second polymerizable monomer comprises a long-chain unsaturated monomer. The mass of the second polymerizable monomer is less than the mass of the second active material. During coating, it spontaneously floats to the surface of the second coating layer. The long-chain unsaturated monomer combines with the initiator in the subsequent electrolyte, polymerizing all unsaturated monomer bonds in the second and first negative electrode coating layers through a high-temperature reaction in the early formation stage. This forms an in-situ coating layer for the silicon-based material, avoiding the low initial efficiency and SEI (solid electrolyte interphase) film damage caused by excessively high active lithium consumption and excessive volumetric strain effects of the silicon-based material. It also ensures the kinetics of the negative electrode system and improves the battery's fast-charging cycle life.
[0051] In some embodiments, the first polymerizing monomer includes at least one selected from acrylamide, N,N-dimethylacrylamide, acrylonitrile, or isocyanate. As an example, the first polymerizing monomer may be acrylamide, N,N-dimethylacrylamide, or acrylonitrile.
[0052] In some embodiments, the second polymerizing monomer includes at least one selected from methyl methacrylate, ethyl acrylate, or pentaerythritol acrylate. As an example, the second polymerizing monomer may be methyl methacrylate or ethyl acrylate.
[0053] In some embodiments, the mass of the first polymer is 3-5% of the mass of the silicon-based active material, based on the mass of the silicon-based active material. For example, the mass of the first polymer can be 3%, 4%, 5%, etc., of the silicon-based active material, or other values within the above range; no specific limitation is made here. If the mass percentage of the first polymer is too low, the silicon-based material in the second negative electrode coating will not be able to form chemical bonds with the surface layer of the first negative electrode coating; if the mass percentage of the first polymer is too high, it will affect the capacity utilization of the first negative electrode active material.
[0054] In some embodiments, the mass of the second polymer is 1-3% of the mass of the silicon-based active material, based on the mass of the silicon-based active material. For example, the mass of the second polymer can be 1%, 2%, 3%, etc., of the silicon-based active material, or other values within the above range; no specific limitation is made here. If the mass percentage of the second polymer is too low, the second polymer on the surface of the second negative electrode coating will not effectively coat the silicon-based material; if the mass percentage of the second polymer is too high, it will affect the capacity utilization of the second negative electrode active material.
[0055] In some embodiments, the carbon-based active material includes at least one of natural graphite or synthetic graphite. As an example, the carbon-based active material may be natural graphite, synthetic graphite, or a mixture of both.
[0056] In some embodiments, the first negative electrode coating further includes a first conductive agent and a first binder.
[0057] In some embodiments, the mass ratio of the first polymer, the first active material, the first conductive agent, and the first binder is (0.6~3):(92~97):(1~3):(1~2). As an example, the mass ratio of the first polymer, the first active material, the first conductive agent, and the first binder can be 0.6:92:1:1, 1.6:95:2:1.5, 3:97:3:2, etc., and of course, other ratios within the above range are also possible, which are not limited here.
[0058] In some embodiments, the first conductive agent includes at least one selected from conductive graphite, conductive carbon black, conductive carbon fiber, carbon nanotubes, or graphene. The conductive carbon black includes acetylene black, Ketjen black, etc. The conductive carbon fiber includes vapor-grown carbon fiber.
[0059] In some embodiments, the first adhesive includes at least one of polyvinylidene fluoride, sodium carboxymethyl cellulose, styrene-butadiene rubber, sodium alginate, or polyacrylic acid.
[0060] In some embodiments, the areal density of the first negative electrode coating is 40-80 g / m³. 2 As an example, the areal density of the first negative electrode coating can be 40 g / m³. 2 60g / m 2 80g / m 2 "etc." can also be other values within the above range, without specific limitations here.
[0061] In some embodiments, the mass content of silicon-based active material in the second active material is ≥20%. As an example, the mass content of silicon-based active material in the second active material can be 20%, 40%, 60%, 80%, etc., or other values within the above range, and is not specifically limited here.
[0062] In some embodiments, the silicon-based active material includes at least one of a silicon-oxygen composite material or a silicon-carbon composite material. As an example, the silicon-based active material may be a silicon-oxygen composite material or a silicon-carbon composite material.
[0063] In some embodiments, the second negative electrode coating further includes a second conductive agent and a second binder.
[0064] In some embodiments, the mass ratio of the second polymer, the second active material, the second conductive agent, and the second binder is (0.2~3):(92~98):(1~3)(1~2). As an example, the mass ratio of the second polymer, the second active material, the second conductive agent, and the second binder can be 0.2:92:1:1, 1.5:95:2:1.5, 3:98:3:2, etc., and of course, other ratios within the above range are also possible, which are not limited here.
[0065] In some embodiments, the second conductive agent includes at least one selected from conductive graphite, conductive carbon black, conductive carbon fiber, carbon nanotubes, or graphene. The conductive carbon black includes acetylene black, Ketjen black, etc. The conductive carbon fiber includes vapor-grown carbon fiber.
[0066] In some embodiments, the second adhesive includes at least one of polyvinylidene fluoride, sodium carboxymethyl cellulose, styrene-butadiene rubber, sodium alginate, or polyacrylic acid.
[0067] In some embodiments, the areal density of the second negative electrode coating is 30-60 g / m³. 2 As an example, the areal density of the second negative electrode coating is 30 g / m³. 2 45g / m 2 60g / m 2 "etc." can also be other values within the above range, without specific limitations here.
[0068] It is understandable that the mass ratios of the first polymer, the first active material, the first conductive agent, and the first binder, as well as the mass ratios of the second polymer and the second conductive agent, and the second conductive agent and the second binder, are related to the electrochemical performance of the corresponding battery and further affect the structural stability of the negative electrode. By controlling the proportions of each substance in the first and second negative electrode coatings within the aforementioned ranges, the roles of each active material and each polymer are fully utilized, effectively improving the cycle performance, fast-charging performance, and structural stability of the negative electrode.
[0069] It is also understandable that the areal density of the coating affects the battery's electrical performance (such as energy density, cycle performance, and rate performance), manufacturing cost, and safety performance. If the areal density of the first and second negative electrode coatings is too high, the electron transport distance increases, electronic resistance increases, and rate performance decreases, adversely affecting the battery's electrical performance and further increasing the difficulty of thermal management. However, if the areal density of the first and second negative electrode coatings is too low, the improvement in the structural stability of the negative electrode sheet is not significant, which will adversely affect the battery's safety and long-term cycle stability.
[0070] In some embodiments, the current collector includes, but is not limited to, at least one of copper foil, nickel foam, nickel mesh, or composite copper foil. As an example, the current collector may be copper foil, may be copper foam, or may be composite copper foil.
[0071] Based on the same inventive concept, embodiments of this application provide a method for preparing a battery, including the following steps: The positive electrode, separator, and negative electrode are arranged in sequence, wound up, injected with electrolyte, left to stand, and then formed and aged to obtain the battery. The electrolyte contains an initiator.
[0072] In this application, the initiator is placed in the electrolyte. After the battery is injected with the electrolyte, a polymerization reaction is carried out at the surface / inner interface of the silicon-based material during the early stage of formation through high temperature reaction (the surface interface refers to the surface of the second negative electrode coating, and the inner interface refers to the surface of the first negative electrode coating). This results in the in-situ formation of a fully encapsulated layer design with silicon-based upper coating, thereby improving the fast-charging cycle performance of silicon-based volume change.
[0073] It should be understood that all the features and advantages described above regarding the "battery" also apply to the "battery manufacturing method," and will not be repeated here.
[0074] In some embodiments, the preparation of the negative electrode includes: A first negative electrode slurry is coated on at least one side of the current collector to obtain a first negative electrode coating. A second negative electrode slurry is coated on the surface of the first negative electrode coating to obtain a second negative electrode coating. The current collector coated with the first negative electrode coating and the second negative electrode coating is dried and cold-pressed.
[0075] In some embodiments, coating at least one side of the current collector with the first negative electrode slurry further includes a drying step at a temperature of 80°C to 100°C.
[0076] In some embodiments, the drying temperature for drying the current collector coated with the first negative electrode coating and the second negative electrode coating is 80°C to 100°C.
[0077] In some embodiments, the compaction density of the cold-pressed material is 1.3~1.7 g / cm³. 3 .
[0078] In some embodiments, the first negative electrode coating includes a first polymeric monomer and a first active material.
[0079] In some embodiments, the second negative electrode coating includes a second polymer monomer and a second active material.
[0080] In some embodiments, the first polymeric monomer accounts for 0.6% to 3% of the total mass of the first negative electrode coating. As an example, the first polymeric monomer can be 0.6%, 1%, 2%, 3%, etc., of the total mass of the first negative electrode coating, or other values within the above range; no specific limitation is made here. If the content of the first polymeric monomer is too low, it will result in insufficient chemical bonding with the silicon-based material in the second negative electrode coating, thus failing to effectively mitigate the adverse effects of the interface breakdown between the first and second negative electrode coatings caused by the volumetric strain of the silicon-based material during fast charging cycles. If the proportion of the first polymeric monomer is too high, the content of the first active material will be relatively low, thereby affecting the battery capacity.
[0081] In some embodiments, the second polymeric monomer accounts for 0.2% to 3% of the total mass of the second negative electrode coating. As an example, the second polymeric monomer can be 0.2%, 1%, 2%, 3%, etc., of the total mass of the second negative electrode coating, or other values within the above range; no specific limitation is made here. If the content of the second polymeric monomer is too low, the integrity of the surface layer of the second negative electrode coating cannot be guaranteed, and it cannot withstand the volumetric strain of the silicon-based active material; if the content of the second polymeric monomer is too high, it will increase the polarization effect of the battery.
[0082] In some embodiments, the mass of the initiator is 0.1 to 0.5% of the total mass of the first and second polymeric monomers in the negative electrode. As an example, the mass of the initiator can be 0.1%, 0.3%, 0.5% of the total mass of the first and second polymeric monomers in the negative electrode, or other values within the above range, which are not specifically limited here.
[0083] In some embodiments, the initiator includes at least one of azobisisobutyronitrile, cumene hydroperoxide, tert-butyl hydroperoxide, di-tert-butyl peroxide, or persulfate.
[0084] In some embodiments, the settling temperature is 60-80°C, and the settling time is 6-12 hours. As examples, the settling temperature can be 60°C, 70°C, 80°C, etc., or other values within the above range; no specific limitation is made here. The settling time can be 6 hours, 8 hours, 10 hours, 12 hours, etc., or other values within the above range; no specific limitation is made here. It is understood that the settling process is the polymerization process of the monomers under the action of the initiator. When polymerization is carried out at low temperatures, a longer settling time is required.
[0085] In this embodiment, the materials and structures of the positive electrode current collector, the conductive agent and the binder in the positive electrode active material layer are not limited, and positive electrode structures and compositions known in the art that can be used in secondary batteries can be selected.
[0086] In this embodiment, the specific material or type of the separator is not limited, and any separator known in the art that can be used in secondary batteries can be selected.
[0087] It should also be noted that the battery in this application does not limit the specific material or type of electrolyte. Any components and types known in the art that can be used in secondary batteries can be selected, as long as the purpose of this application can be achieved.
[0088] Therefore, based on the above solution, this application addresses the issues of surface and inner interfaces caused by the double-layer coating of silicon-based materials in fast-charging design requirements, proposing a full-coverage design for silicon-based material coating. This coating layer can chemically bond to the inner interface of the underlying layer, ensuring the overall stability of the negative electrode in the later stages of cycling. This coating layer constructs a uniform and thin surface interface in situ, allowing for initial polymerization on the electrode surface during the early formation phase, thereby reducing active lithium consumption. Furthermore, the in-situ polymerized interface protective film can effectively withstand the volumetric strain effect of the silicon-based material, protecting interface integrity and stability, thus improving initial efficiency and fast-charging capability. Therefore, the battery of this application has high initial efficiency and high fast-charging cycle life.
[0089] The following describes the implementation methods of this application. The implementation methods described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the implementation methods, they shall be performed in accordance with the techniques or conditions described in the literature in this field or according to the product instructions. Reagents, materials, or instruments used, unless otherwise specified, are all conventional products that can be obtained commercially.
[0090] Example 1 Preparation of negative electrode sheet Artificial graphite, conductive carbon black Super P (SP), single-walled carbon nanotubes (SWCNT), polyacrylic acid (PAA), styrene-butadiene rubber (SBR), and acrylamide (AM) were mixed in a mass ratio of 94.2:1.42:0.08:1.9:0.9:1.5. Deionized water was added and the mixture was stirred to form a uniform slurry, which yielded the first active slurry. The first active slurry was uniformly coated onto the side of the negative electrode current collector (8μm copper foil) and dried (at a drying temperature of 90℃) to obtain the first negative electrode coating.
[0091] A silicon-oxygen composite material, SP, PAA, SBR, and methyl methacrylate (MMA) were mixed in a mass ratio of 96.5:1:1.3:0.7:0.5. Deionized water was added and the mixture was stirred to form a homogeneous slurry, yielding a second active slurry. This second active slurry was coated onto the surface of the first negative electrode coating, dried (at 90°C), and then cold-pressed (compacted density 1.5 g / cm³). 3 This yields the negative electrode.
[0092] Preparation of positive electrode sheet The positive electrode active material (lithium nickel cobalt manganese oxide LiNi) 0.8 Co 0.1 Mn 0.1 SP, carbon nanotubes, and polyvinylidene fluoride (PVDF5130) binder are mixed in a ratio of 97:1.6:0.4:1. N-methylpyrrolidone (NMP) is added and stirred to form a uniform and stable positive electrode slurry. The positive electrode slurry is uniformly coated on the positive electrode current collector (13μm aluminum foil), dried, and cold-pressed to obtain the positive electrode sheet.
[0093] Separating membrane A polyethylene (PE) membrane with a thickness of 12μm was selected as the separator.
[0094] Preparation of electrolyte In a glove box filled with inert gas, ethylene carbonate, methyl ethyl carbonate, and diethyl carbonate were mixed in a mass ratio of 1:1:1 to obtain an organic solvent. Then, lithium salt LiPF6 was dissolved in the organic solvent at a concentration of 1.2 mol / L, and an initiator of 0.2% of the total mass of the monomers was added to obtain the electrolyte.
[0095] Battery manufacturing The positive electrode, separator, and negative electrode are arranged in sequence and assembled by winding. The electrolyte is injected into the dry cell and immersed at room temperature for 12 hours. After standing at 70°C for 10 hours, formation is carried out at 45°C. The formation process is as follows: charge at 0.05C to 3.4V, then charge at 0.2C to 3.75V. After aging at room temperature for 24 hours, capacity testing is performed: charge at 1C to 4.25V, then discharge at 1C to 2.5V to obtain the battery.
[0096] Examples 2-10 The differences between Examples 2-10 and Example 1 are shown in Table 1. All contents not mentioned in the table are the same as those in Example 1.
[0097] Comparative Examples 1-11 The differences between Comparative Examples 1-11 and Example 1 are shown in Table 1. All contents not mentioned in the table are the same as those in Example 1.
[0098] Table 1 Note: In Table 1, AM refers to acrylamide, MMA refers to methyl methacrylate, PETA refers to pentaerythritol acrylate, and " / " indicates that the substance was not added or that the step was not involved.
[0099] Performance testing (1) First Coulomb efficiency test: Record the total charge C1 and total discharge C2 during the capacity formation stage, and obtain the first Coulomb efficiency test = C2 / C1*100%.
[0100] (2) Fast charging cycle test: 1) Place the battery in a constant temperature chamber at 25℃ for 30 minutes, and charge it to 4.25V at a constant current of 2C; 2) After placing the battery in a constant temperature chamber for 30 minutes, discharge it to 2.5V at a constant current of 1C, and record the initial discharge capacity C1; 3) Cycle 1)~2) until the battery discharge capacity is lower than 80% of the initial discharge capacity C1, and stop the test, and record the discharge capacity Cn, where n is the number of cycles.
[0101] The test results of each embodiment and comparative example are shown in Table 2.
[0102] Table 2 Note: The silicon-based material layer refers to the silicon-based material layer in the second negative electrode material.
[0103] The parts of this invention not described in detail are techniques known to those skilled in the art.
[0104] The basic principles of the present invention have been described above with reference to specific embodiments. However, it should be noted that the advantages, benefits, and effects mentioned in the present invention are merely examples and not limitations, and should not be considered as essential features of each embodiment of the present invention. Furthermore, the specific details disclosed above are for illustrative and facilitative purposes only, and are not limitations. These details do not limit the present invention to the necessity of employing the aforementioned specific details.
[0105] It should be noted that the terms "and / or" or " / " used herein are merely descriptions of the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, or B existing alone. The singular forms "a," "described," and "the" used in the embodiments of the invention and the appended claims are also intended to include the plural forms, unless the context clearly indicates otherwise.
[0106] In the detailed description and claims, a list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, then the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, then the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may contain a single element or multiple elements. Item B may contain a single element or multiple elements. Item C may contain a single element or multiple elements.
[0107] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A battery, comprising a positive electrode, a separator, a negative electrode, and an electrolyte, characterized in that, The negative electrode includes: current collector; A first negative electrode coating is disposed on at least one side surface of the current collector along the thickness direction, and the first negative electrode coating comprises a first polymer and a first active material; The second negative electrode coating is disposed on the surface of the first negative electrode coating away from the current collector, and the second negative electrode coating includes a second polymer and a second active material; Wherein, the first polymer is located on the surface layer of the first negative electrode coating on the side away from the current collector; The second polymer is located on the surface of the second negative electrode coating on the side away from the first negative electrode coating; The first active material includes a carbon-based active material; the second active material includes a silicon-based active material; the first polymer is obtained by polymerization of a first polymeric monomer. The first polymeric monomer includes an amino- and / or nitrile-containing polymeric monomer; The second polymer is obtained by polymerization of a second monomer; The second polymerizable monomer comprises long-chain unsaturated monomers; The electrolyte includes an initiator; the first polymeric monomer and the long-chain unsaturated monomer combine with the initiator to form the first polymer and the second polymer, respectively.
2. The battery according to claim 1, characterized in that, The first polymerizing monomer includes at least one of acrylamide, N,N-dimethylacrylamide, acrylonitrile, and isocyanate; And / or, the second polymerizing monomer includes at least one of methyl methacrylate, ethyl acrylate, and pentaerythritol acrylate.
3. The battery according to claim 1, characterized in that, Based on the mass of the silicon-based active material, the mass of the first polymer is 3-5% of the mass of the silicon-based active material; And / or, based on the mass of the silicon-based active material, the mass of the second polymer is 1 to 3% of the mass of the silicon-based active material.
4. The battery according to claim 1, characterized in that, The first negative electrode coating satisfies at least one of the following features (1) to (3): (1) The carbon-based active material includes at least one of natural graphite and artificial graphite; (2) The first negative electrode coating further includes a first conductive agent and a first binder; The mass ratio of the first polymer, the first active material, the first conductive agent, and the first binder is (0.6~3):(92~97):(1~3):(1~2); (3) The areal density of the first negative electrode coating is 40-80 g / m³. 2 .
5. The battery according to claim 1, characterized in that, The second negative electrode coating satisfies at least one of the following features (1) to (4): (1) The mass content of silicon-based active material in the second active material is ≥20%; (2) The silicon-based active material includes at least one of silicon-oxygen composite material or silicon-carbon composite material; (3) The second negative electrode coating further includes a second conductive agent and a second binder; The mass ratio of the second polymer, the second active material, the second conductive agent, and the second binder is (0.2~3):(92~98):(1~3):(1~2); (4) The areal density of the second negative electrode coating is 30-60 g / m³. 2 .
6. The method for preparing the battery according to any one of claims 1 to 5, characterized in that, Includes the following steps: The positive electrode, separator, and negative electrode are arranged in sequence, wound up, injected with electrolyte, left to stand, and then formed and aged to obtain the battery. The electrolyte contains an initiator.
7. The method for preparing a battery according to claim 6, characterized in that, The preparation of the negative electrode includes: A first negative electrode slurry is coated on at least one side of the current collector to obtain a first negative electrode coating. A second negative electrode slurry is coated on the surface of the first negative electrode coating to obtain a second negative electrode coating. The current collector coated with the first negative electrode coating and the second negative electrode coating is dried and cold-pressed; The first negative electrode coating comprises a first polymeric monomer and a first active material; The second negative electrode coating includes a second polymer monomer and a second active material; The first polymeric monomer accounts for 0.6-3% of the total mass of the first negative electrode coating; The second polymeric monomer accounts for 0.2-3% of the total mass of the second negative electrode coating; The mass of the initiator is 0.1 to 0.5% of the total mass of the first and second polymerizing monomers in the negative electrode.
8. The method for preparing a battery according to claim 6, characterized in that, The initiator includes at least one of azobisisobutyronitrile, cumene hydroperoxide, tert-butyl hydroperoxide, di-tert-butyl peroxide, or persulfate.
9. The method for preparing a battery according to claim 6, characterized in that, The settling temperature is 60~80℃, and the time is 6~12h.
Citation Information
Patent Citations
Secondary battery, electric equipment and preparation method of secondary battery
CN118198257A
Negative plate and battery
CN118676308A